Implementation of a model of awareness-raising for taxi motorcyclists in Benin in relation to helmet use: protocol for a quasi-experimental study - Bella Hounkpe Dos Santos; Alphonse Kpozehouen; Yolaine Glele Ahanhanzo; Donatien Daddah; Edgard-Marius Ouendo; Alain Leveque; Yves Coppieters (BMC, 2021)
Abstract Background In the large cities of Benin, motorcycle taxi drivers, mainly between the ages of 20 and 40, are particularly exposed to accidents due to their profession. User awareness, along with legislative reforms and enforcement measures, would reduce the incidence of crashes and injuries. This study aims to test the effectiveness of an awareness-raising model regarding helmet use for motorcycle taxi drivers. Methods This is a quasi-experimental study that will take place in the cities of Parakou (intervention group) and Porto Novo (control group). Over a three-month period, a package of awareness-raising activities will be implemented in the intervention area, targeting a group of motorcycle taxi drivers. The messages to be developed for awareness-raising will focus on the most frequently influencing factors, as identified by the baseline collection. These key messages will be disseminated through various tools and communication channels (banners, motorcycle stickers and motorcycle taxi uniforms, interactive sessions). Data will be collected prospectively via a self-reported questionnaire and observation, carried out before the intervention, at the end, and 6 months later. The data will relate to knowledge, attitudes and practices regarding helmet use. The analysis will compare the indicators between the groups, as well as between the pre- and post-intervention phase. The KoboCollect software will be used for data entry and processing, and Stata 15 will be used for data analysis. Chi-square or Fisher, Student's or Kruskal-Wallis tests will be used for the comparisons. The difference-in-difference method will be used to determine the specific effect of the awareness activities. Discussion This study will assess the contribution of awareness messages to changing the behaviour of motorcycle taxi drivers by determining the specific effect of the intervention.